Asphaltic Concrete Pavement Strength and the Impact of Rainfall - GOC Amuchi; Prof. J.C Agunwamba (International Journal of Engineering and Management Research, 2021)
Studies have shown that moisture impacts on the strength of flexible pavement surface of asphaltic concrete. Several investigations and relevant researches treated the effect of subsurface and surface water sources, on the durability of flexible pavements. This study is focused on the surface water sources, as a result of precipitation (rainfall), on the surface of flexible pavements. To conduct this experiment, the considerations made include (i) the continuous exposure of the pavement surface to annual rainfall (ii) application of pavement exposure to moisture in the field. This study considered the amount of rainfall each day, as the duration (age) of pavement exposure to moisture (being under water during rainfall). For the purpose of this experiment, the Owerri to Onitsha about 90km of dual carriage way in south east of Nigeria, was considered. This is a flexible pavement that traverses through the rain forest belt, characterized with high amount of annual rainfall values. Flexible pavement specimens from this road were obtained, cleaned and immersed in water after weighing, to keep vital records of the necessary parameters, before further tests at 7days intervals. Values of strength obtained after days in water, that approximated to the appropriate field situation of exposure to rainfall, showed a consistent loss of strength, from the crushing strength results.